Non-invasive monitoring of hydraulic surge propagation in a wounded tobacco plant - Nožková, Vladimíra; Šmíd, Petr; Horváth, Pavel; Hrabovský, Miroslav; Ilík, Petr (Plant methods, 2018)
BACKGROUND: When a plant is wounded, a rapid hydraulic surge, acting probably as a systemic signal, spreads from the site of injury throughout the plant and leads to small transient deformation of tissues. So far, the propagation of hydraulic surge has been monitored by contact and thus potentially invasive methods. RESULTS: Here we present a non-invasive optical method, which allows simultaneous monitoring of micrometric shift of two opposite stem margins. The usefulness of this method was demonstrated by the measurement of the hydraulic surge propagation in a tobacco (Nicotiana tabacum (L.) cv. Samsun) after burning of its upper leaf. We have observed transient narrowing the stem below the burned leaf, which started within a few minutes after local burning. The comparison of the shift of the stem margin following vascular trace of the burned leaf and the margin on the opposite side of the stem has revealed that the stem deformation is highly asymmetric. CONCLUSIONS: This optical method represents a novel tool to investigate the mechanism of systemic response of plants to local damage. Our results points out the complexity of the relationship between hydraulic surge propagation and stem deformation.
Keywords: Tobacco; Hydraulic surge; Light diffraction; Stem deformation; Local burning